PEMANFAATAN LIMBAH MINYAK JELANTAH MENJADI SABUN CUCI PIRING YANG AMAN DIGUNAKAN - A Tenriugi Daeng Pine; Yuyun Sri Wahyuni; Nurul Hidayah Base; Yusriyani; Maulana Imansyah Zulkarnain (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2023)
Waste cooking oil has been a household waste that is not utilized so it can pollute the environment. The activities carried out aim to provide education and skills in making dish soap from waste cooking oil. Community service activities in Sunggumanai Village, Pattallassang District, Gowa Regency. Community service activities are carried out in the form of direct training for PKK mothers and housewives who live in the area. The soap made from used cooking oil was then tested on the foam and its cleaning ability and a debriefing and questionnaire was conducted on the participants who attended the training. Training on making dishwashing soap from used cooking oil received a positive response and provided knowledge and skills to the people of Sunggumanai Village in processing waste cooking oil into dishwashing soap that is safe to use.